Curriculum Analysis of Biological Learning Media Module Development Based on Project Based Learning (PjBL) - Diana Susanti; Liza Yulia Sari; Vivi Fitriani (Jurnal Penelitian Pendidikan IPA, 2020)
Biology Learning Media Course requires students to be able to produce biology learning media. In the previous recovery, students were less creative in producing media for Biology. So students are less able to create suitable media. During this time students do not have the right learning resources in exploring creativity. For this reason, the development of project-based learning based modules is carried out to provide appropriate learning resources and increase student creativity. The purpose of this study was to determine curriculum analysis for the development of media learning modules based on pjbl. Research is a research development using the 4D model at defined stage. Curriculum analysis data were obtained through descriptive analysis. The results showed that 9 materials needed development in the module including communication, learning media, classification of educational media, characteristics of students and their relation to the biology learning media, the role of media in achieving learning objectives, multimedia, photography and video shooting, designing, presenting and displaying, of biology media, media scenarios biology learning. It can be concluded that there are nine materials in developing a learning media module based on PjBL.